Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Tony Irawan (Faculty of Economic & Business Universitas Gadjah Mada, 2012)
NO. Penulis ---- Judul Artikel ---- Halaman 1. Tony Irawan, Djoni Hartono, Ferry Irawan dan Arief Anshory Yusuf ---- Infrastructure Improvement and Its Impacts on the Indonesian Economic Performance ---- 293-302 2. Taswan, Eduardus Tandelilin, Suad Husnan dan Mamduh M. Hanafi ---- Bank Risk and Market Discipline ---- 303-314 3. Setiyono Mihardjo dan Sumiyana ---- Private Information Arrival at Indonesia Stock Exchange, Reality or Imaginary? U-Shaped Return Variance Curve Verifications ---- 315-335 4. Rahel Widiawati Kibal, Agus Suman, Khusnul Ashar dan Asfi Manzilati ---- Social Capital in Non-Barter Transaction Chain in Pasar Blante Kawangkoan, North Sulawesi Province ---- 336-354 5. Ranti Yulia Wardani dan Sony Warsono ---- A Cross-Cultural Study on The Value Structure of Mobile Internet Usage : Comparison Between Indonesia and Japan ---- 355-372 6. Inayati Nuraini Dwiputri ---- Hidden Action in the Case of Tax Dispustes in Indonesia ---- 373-389 7. Sri Wahyuni dan Jogiyanto Hartono ---- Reminder Effect and Anchoring-Adjustment in Earnings Announcement : Implementation of Prior-Periode Benchmark Disclosure Strategy ---- 390-405 8. Lina Fandianto and Eddy M. Sutanto ---- Effectiveness Analysis of Shangri-La Academy Program Towards Employees Working Motivation at Shangri-La Hotel Surabaya ---- 406-418